2022
DOI: 10.1017/ice.2022.105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of coronavirus disease 2019 (COVID-19) symptoms at diagnosis among healthcare personnel before and after the emergence of the omicron variant

Abstract: We used a self-reporting system to compare symptom frequency of hospital personnel with coronavirus disease 2019 before and after the emergence of the Omicron variant. Omicron was more likely to result in asymptomatic carriage (7% vs 12%; P = .009), and fewer symptoms were observed in those with booster vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 6 publications
0
20
2
Order By: Relevance
“…The proportion of asymptomatic infection in our cohort was lower than studies described previously from South Africa (23%) and China (46.7%) but was similar to a cohort of healthcare personnel from New York (11%) during Omicron epidemic. [19,20,21] The actual proportion of asymptomatic infection in our cohort could be overestimated as the clinical data could have been submitted during pre-symptomatic stage of infection. Although being symptomatic and having exposure history were the most common reasons for undergoing testing, regular mandatory RAT played an important role in promote testing as up to 26.66% of the infected staff were identified as a result of such policy.…”
Section: Discussionmentioning
confidence: 97%
“…The proportion of asymptomatic infection in our cohort was lower than studies described previously from South Africa (23%) and China (46.7%) but was similar to a cohort of healthcare personnel from New York (11%) during Omicron epidemic. [19,20,21] The actual proportion of asymptomatic infection in our cohort could be overestimated as the clinical data could have been submitted during pre-symptomatic stage of infection. Although being symptomatic and having exposure history were the most common reasons for undergoing testing, regular mandatory RAT played an important role in promote testing as up to 26.66% of the infected staff were identified as a result of such policy.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Bhattacharya et al reported that fever and loss of smell are important predictors for the diagnosis of COVID-19 [ 10 ]. However, it should be noted that different clinical characteristics were reported for each epidemic strain of COVID-19 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This should be done in the future to verify differences between ethnicities, and this may also “sharpen” the ethnic distinctions which may be blurred by ethnically mixed cohorts. For example, the large fraction of Asians and/or Latinos/Hispanics in the cohorts of Weil et al [48] and (likely) of Laracy et al [49] may explain the relatively low overall prevalence of hyposmia in their studies. Although ethnic patterns are emerging, more detailed analyses in future studies may allow to assign a more precise prevalence of olfactory dysfunction to each major ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…2). Twenty-two studies were from populations primarily of European ancestry [8,32,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], eight studies on East Asians [60][61][62][63][64][65][66][67], three studies on South Asians [68][69][70], three studies on Latinos [71][72][73], four studies on populations in Africa [74][75][76][77], and one study from West Asia (Turkey [78]). The location of studies, with the prevalence indicated by the color intensity, and the cohort size indicated by the size of the circles, shows that Western countries report the highest prevalence, while studies from East Asia and Africa report the lowest prevalence (Fig.…”
Section: Properties Of Studiesmentioning
confidence: 99%